2007
DOI: 10.1007/s00213-007-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the sensitivity of operant timing behaviour to stimulation of D1 dopamine receptors

Abstract: Stimulation of D(1)-like dopamine receptors affects performance in the free-operant psychophysical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 59 publications
4
17
0
Order By: Relevance
“…Firstly, the role of D1 and D2 receptors in timing in the seconds to minutes range appears to be task dependent, as a number of recent studies have shown evidence for D1 involvement in timing in this range, using tasks that were not used in earlier studies showing D2 involvement ( e.g. [140][143]). Additionally, several studies showing D2 involvement in earlier tasks also showed D1 involvement ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the role of D1 and D2 receptors in timing in the seconds to minutes range appears to be task dependent, as a number of recent studies have shown evidence for D1 involvement in timing in this range, using tasks that were not used in earlier studies showing D2 involvement ( e.g. [140][143]). Additionally, several studies showing D2 involvement in earlier tasks also showed D1 involvement ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has long been hypothesized that dopamine overactivity is related to schizophrenia [5][6][7] , and an important brain region where neurotransmitter activity contributes to schizophrenic symptoms is the striatum 3,8,9 , which is known to be involved in the control of timing 10,11 . Changes in dopamine activity also influences performance in timing tasks 9,12 ; increased dopamine activity in the striatum slows subjective time-perception, making subjects over-estimate the passage of time 13,14 . Although multiple mechanisms may be responsible for dopamine-related disruption of time-perception in schizophrenia (e.g., impact on pacemakers and accumulators, working and reference memory, and comparator processes 15 ), the episodic nature of schizophrenia 16,17 , and the changes in potentiallyassociated dopaminergic levels 6,7 , suggest that individuals in an acute phase of the disorder, or not on medication, might be particularly prone to altered time-perception and that such time-perception effects may be variable.…”
Section: Introductionmentioning
confidence: 99%
“…Other timing research has reported the disruption of timing precision as a result of manipulating motivation-related variables (Balci, Ludvig, & Brunner, 2010;Galtress & Kirkpatrick, 2009;Ludvig, Balci, & Spetch, 2011;Plowright, Church, Behnke, & Silverman, 2000;Ward & Odum, 2006, disruptions in attention (Buhusi & Meck, 2006a, 2006bWard & Odum, 2007) pharmacological manipulations that target the neurotransmitter dopamine (e.g., Body, Cheung, Valencia-Torres, Olarte-Sanchez, Fone, Bradshaw, & Szabadi, 2013;Cheung et al, 2007;Odum, 2002). How different time markers might affect temporal control of behavior has received little attention by comparison; however, recent research suggests that it may be an important variable (Caetano & Church, 2009;Fox & Kyonka, 2013, 2015.…”
Section: Discussionmentioning
confidence: 99%